The impact of urban expansion on the vegetation cover in the city of Baqaa using geographic information systems during the period (1990-2024 AD) - Al-Shammari, Seham Sayer Khalif (Journal of agricultural, environmental and veterinary sciences, 2025)
Vegetation cover is fundamental to life on Earth, and its deterioration poses a significant threat to the natural environment, contributing to increasingly extreme climatic changes as well as drought and desertification. The decline in vegetation cover also adversely affects the relationship between humans and the environment, disrupting the balance within ecosystems and leading to soil degradation.The Kingdom of Saudi Arabia has witnessed rapid and monumental urban growth, particularly in cities such as Baqaa, where the population has surged, resulting in extensive urban expansion that encroaches upon the natural environment and vegetation cover. This necessitates the implementation of sustainable planning policies and the development of green areas within urban settings, aligned with the comprehensive national vision for 2030 (Al-Zamil & Al-Qarni, 2019, p.1). Moreover, urban sprawl into green spaces is a primary cause of vegetation decline, as swift technological advancement and accelerating population growth heighten the demand for housing and urban development, thereby exacerbating the pressure on ecological systems (Al-Sanousi & Al-Shahab, 2018, p.40).  This study has examined the impact of urban expansion in Baqaa on vegetation cover over a span of thirty years, utilizing Geographic Information Systems (GIS) and remote sensing. It highlights the initiatives undertaken in the region to preserve the natural environment in accordance with the Kingdom’s Vision 2030, identifying green areas that require protection and proposing their future development into exceptional recreational and tourist destinations, thereby safeguarding the environmental context climatically and health-wise through their positive influence on climate and reduction of pollution from human waste.
Keywords: Urban expansion; Geographic Information Systems; Remote sensing